2021
DOI: 10.3389/fpsyg.2021.754047
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Impact of the COVID-19 Pandemic on Healthcare Professionals in Tunisia: Risk and Protective Factors

Abstract: Background: Our study aimed to evaluate the magnitude of different psychological outcomes among Tunisian healthcare professionals (HCPs) during the first wave of the coronavirus disease 2019 (COVID-19) pandemic, and to identify the associated factors.Methods: Healthcare professionals completed a cross-sectional questionnaire during a 3-week period in the first wave of the COVID-19 pandemic in Tunisia. The survey collected demographic information, factors that may interfere with the psychological outcomes, beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…During the COVID-19 epidemic, health professionals, directly engaged in fight against COVID-19, experience chronic fatigue and stress ( Hammami et al, 2021 ). Medical workers also display compassion fatigue, burnout ( Gawrych, 2021 ; Neto et al, 2020 ), and mental exhaustion ( Alharbi, Jackson & Usker, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 epidemic, health professionals, directly engaged in fight against COVID-19, experience chronic fatigue and stress ( Hammami et al, 2021 ). Medical workers also display compassion fatigue, burnout ( Gawrych, 2021 ; Neto et al, 2020 ), and mental exhaustion ( Alharbi, Jackson & Usker, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among those selected study, most of the study found cross-sectional study (Patra et al , 2020; Phillipou et al , 2020; Ripon et al , 2020; Sankar et al , 2020; López-Moreno et al , 2020; Al-Domi et al , 2021; Ali et al , 2021; Sińska et al , 2021; Vu et al , 2021; Wei et al , 2021; Ceulemans et al , 2021; Chi et al , 2021; Hammami et al , 2021; Jonikas et al , 2021; Madan et al , 2021; Niermann, Bollenbach and Kanning, 2022; Lorenzoni et al , 2022; Mekkawy, 2022), retrospective study (Błaszczyk-Bębenek et al , 2020; Almandoz et al , 2021; Valenzise et al , 2021), literature review (Neira et al , 2021; Andersson et al , 2022), review and mini-review (Arora and Grey, 2020; Bennett et al , 2021; Scapaticci et al , 2022), longitudinal study (Zhang et al , 2020a, 2020b; Herle et al , 2021; Sebastian et al , 2021) and online survey included (Vally and Helmy, 2021; Wilson et al , 2021; Woodruff et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Mental health, dietary habits and physical activity were studied in (Ripon et al , 2020; Ali et al , 2021; Chi et al , 2021; Wei et al , 2021; Wilson et al , 2021; Woodruff et al , 2021; Lorenzoni et al , 2022), Mental health and weight-related behavior included in (Almandoz et al , 2021; Madan et al , 2021; Valenzise et al , 2021), physical activity and motivation (Andersson et al , 2022; Niermann, Bollenbach and Kanning, 2022), health behavior (Arora and Grey, 2020; Al-Domi et al , 2021; Woodruff et al , 2021), lifestyle and dietary habits (Sankar et al , 2020; Bennett et al , 2021; Madan et al , 2021; Neira et al , 2021; Scapaticci et al , 2022), mental health status in pregnant and lactating (Zhang et al , 2020a, 2020b; Ceulemans et al , 2021), eating behavior (Błaszczyk-Bębenek et al , 2020; Phillipou et al , 2020; Herle et al , 2021; Sińska et al , 2021; Vu et al , 2021), mental health and behavioral health disorder (Hammami et al , 2021; Jonikas et al , 2021; Vally and Helmy, 2021; Mekkawy, 2022), food habits (López-Moreno et al , 2020) and school closure and screen (Patra et al , 2020; Woodruff et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
“…and the French version of Maslach Burn out Inventory (MBI-HSS) [16] to assess the level of burnout. This psychometric instrument consists of 22 items evaluating three dimensions of burnout: Occupational exhaustion (EE) (nine items): 1, 2, 3,6,8,13,14,16,20…”
Section: Data Collection and Variable Definitionsmentioning
confidence: 99%
“…Although a few Tunisian studies have shown that some caregivers may suffer from psychological impact such depression, anxiety, and insomnia [12][13][14], no study has yet looked at burnout among health workers during this pandemic.…”
Section: Introductionmentioning
confidence: 99%